From Genius Loci to Pachamama. A Revalorization of the Spirit of Place in the Face of Neo-extractivisms in Latin America (Andamios, Revista de Investigación Social, 2025)
Based on the classic concept of Genius Loci, this article proposes to reflect on its link with the South American notion of Pachamama to turn our gaze toward the spirit of the place, the environment and Mother Earth. Focusing on Latin America and using a qualitative methodology, it addresses the main anthropic actions led by economic development that have had and continue to impact our common home. It focuses primarily on the concept of neo-extractivism, identifying different variants and debates about its significant effects, and critically analyzing the actions that various countries have carried out to protect the rights of Mother Earth and all its components and living beings.
Keywords: Genius Loci; Pachamama; neoextractivism; coloniality; alternatives